A Practical Approach to Nuclear Physics - Varier, K. Muraleedhara, author (Oxford, UK : Alpha Science International Ltd, 2019)
A PRACTICAL APPROACH TO NUCLEAR PHYSICS contains preliminary Nuclear Physics experiments and advanced level experiments for the students. This book is segregated in four categories, viz., Familiarization experiments, Preliminary experiments, Research level experiments and Accelerator based experiments